Antara Dogma dan Pragmatisme: Menyelaraskan Metodologi Ganda Ibn Taymiyyah dalam Teologi dan Hukum - Fauzi, Irfan; Moh. Fadllurrahman (CV Kalimasada Group, 2025)
This article addresses the apparent paradox in Ibn Taymiyyah's thought: his reputation for rigid literalism in theology contrasted with his flexibility and contextualism in socio-political law. This study aims to demonstrate that this distinction represents not an inconsistency, but rather a conscious and coherent strategy of epistemological demarcation. Employing a qualitative library research method, the study utilizes socio-historical readings and content analysis of Ibn Taymiyyah's key concepts within the realms of creed (aqidah) and jurisprudence/politics (fiqh/siyasah). The findings indicate that Ibn Taymiyyah distinguishes revelatory texts based on the character of their objects: theological verses are positioned as a tawqifi domain demanding submission (taslim) without philosophical speculation, whereas legal verses are understood through a maqashidi lens, opening space for independent reasoning (ijtihad) to achieve public benefit (maslahah). This pattern is consistent in his reading of divine attribute verses (e.g., Q.S. Ṭāhā: 5), which tends to be affirmative without metaphorical interpretation (ta'wil), and in his contextual approach to public law issues, such as limiting the application of war verses (e.g., Q.S. At-Taubah: 5) through historical context and legal objectives. These findings correct simplistic binary labelings of Ibn Taymiyyah and help explain the error of certain contemporary groups who inappropriately transpose theological rigidity into the public legal sphere, which ought to remain responsive.